Hubungan Pengetahuan Gizi, Eating Behavior, dan Asupan Ultra Processed Foods dengan Status Gizi Pelajar SMA Muhammadiyah 2 Surabaya - Alyssia Anindia Putri Nayla Sekarhati (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Nutritional problems among adolescents remain a public health concern in Indonesia due to their association with an increased risk of non-communicable diseases later in life. Changes in dietary patterns characterized by increased consumption of ultra-processed foods (UPFs), unhealthy eating behaviors, and inadequate nutritional knowledge are considered important factors influencing adolescents' nutritional status. This study aimed to analyze the relationship between nutritional knowledge, eating behavior, and ultra-processed food intake with the nutritional status of students at SMA Muhammadiyah 2 Surabaya. This study employed an analytical observational design with a crosssectional approach. Participants were selected using proportional random sampling. Nutritional knowledge was assessed using a nutrition knowledge questionnaire, eating behavior was measured using the Dutch Eating Behavior Questionnaire (DEBQ), and ultra-processed food intake was collected using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Nutritional status was determined using Body Mass Index-for-Age (BMI-for-Age). Data were analyzed using the ChiSquare test with a significance level of α=0.05. The results showed no significant association between nutritional knowledge and nutritional status (p=0.113), external eating and nutritional status (p=0.142), energy intake from UPFs and nutritional status (p=0.365), or fat intake from UPFs and nutritional status (p=0.087). However, significant associations were found between emotional eating and nutritional status (p=0.023), as well as restrained eating and nutritional status (p=0.012). This study concludes that eating behavior dimensions, particularly emotional eating and restrained eating, are associated with the nutritional status of students at SMA Muhammadiyah 2 Surabaya. Therefore, efforts to promote healthy eating behaviors and improve self-regulation in managing dietary habits among adolescents are needed.